Advancing Atmospheric Thermodynamic Sounding from Space using Hyperspectral Microwave Measurements - Gambacorta, Antonia; Piepmeier, Jeffrey; Stephen, Mark; Santanello, Joseph; Blaisdell, John; Moradi, Isaac; McCarty, William; Rosenberg, Robert; Kotsakis, Alexander; MacKinnon, James; Gambini, Fabrizio; Mohammed, Priscilla; et al. (IEEE, 2023)
We present a comprehensive sensitivity analysis and geophysical retrieval product demonstration to assess the enhanced information content in atmospheric temperature and water vapor, harnessed in hyperspectral microwave measurements. A particular focus of this study is devoted to quantifying and comparing the impact on retrieval performance resulting from novel spectral bands of the microwave thermal spectrum, by means of data addition and data denial trade studies. Various spectral configurations are assessed, each reflecting specific technology solutions intended to maximize geophysical product performance within feasible size, weight, power and cost constraints. Our results indicate that the use of a hyperspectral sampling in the oxygen and water vapor sounding lines alone provides significant improvements in the lower and free tropospheric thermodynamic fields (up to ∼40%), when compared against the program of record (i.e., the Advanced Technology Microwave Sounder, ATMS). Our experiments also demonstrate the essential role played by extending the coverage in the window regions, leading to an overall improvement of up to ∼50% in the Earth's Planetary Boundary Layer thermodynamic fields. This work concludes with an overview on the state of the art in hyperspectral microwave technology and a discussion on future applications of interest to numerical weather prediction (NWP) and climate science. The work presented in this study focuses on ocean, clear-sky demonstrations. All-sky, all-surface investigations will be the focus of a follow-up study, as we advance our capability to simulate more complex scenarios and improve scene variability.